The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1021/ic9705711
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer in Covalently Linked Oxomolybdenum(V) Porphyrin Systems

Abstract: The pterin-containing molybdenum enzymes are comprised of three general classes which perform simple oxygen-atom transfer either to or from substrate (sulfite oxidase and DMSO reductase families) and the oxidative hydroxylation of various substrates (xanthine oxidase family). 1 Following oxygen-atom transfer, the resting state of the enzyme is regenerated by two sequential one-electron transfers. Therefore, it is of interest to investigate electron transfer events in oxomolybdenum systems which mimic specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The disadvantages associated with first generation PSs have led to extensive investigation aimed at improving the efficacy of PS molecules via alteration of the peripheral functionality of the porphyrin 33 , or direct modification of the porphyrin core 34 , The following the seminal works on the first generation PS have resulted in the production of several new non-porphyrinoid PS molecules ( Fig. 2 ).…”
Section: The Photosensitizers For Anticancer Pdtmentioning
confidence: 99%
“…The disadvantages associated with first generation PSs have led to extensive investigation aimed at improving the efficacy of PS molecules via alteration of the peripheral functionality of the porphyrin 33 , or direct modification of the porphyrin core 34 , The following the seminal works on the first generation PS have resulted in the production of several new non-porphyrinoid PS molecules ( Fig. 2 ).…”
Section: The Photosensitizers For Anticancer Pdtmentioning
confidence: 99%
“…Enemark and Kirk et al already demonstrated in an early study that a Mo center can be photoactivated via an antenna-mediated electron transfer process by covalently linking an oxo-Mo(V) unit to porphyrin-Fe(III) or Zn(II) complexes (Scheme 1a). 18,19 Although catalytic investigations were not reported for these dyads, the study highlighted photoactivation as a potential way of initiating intercomponent electron transfer. More recently, Heinze et al appended two redox-active ferrocene units to a cisdioxo-Mo(VI) complex to mimic the electron-transfer chain in the molybdenum enzyme sulfite oxidase (Scheme 1b).…”
Section: ■ Introductionmentioning
confidence: 91%
“…Since Mo is chosen by nature as OAT catalyst par excellence based on its ability to redox cycle between oxidation states VI, V, and IV, we are interested in utilizing bioinspired Mo complexes as catalysts in dyads designed to facilitate substrate oxidation via a photoredox process. Enemark and Kirk et al already demonstrated in an early study that a Mo center can be photoactivated via an antenna-mediated electron transfer process by covalently linking an oxo-Mo­(V) unit to porphyrin-Fe­(III) or Zn­(II) complexes (Scheme a). , Although catalytic investigations were not reported for these dyads, the study highlighted photoactivation as a potential way of initiating intercomponent electron transfer. More recently, Heinze et al appended two redox-active ferrocene units to a cis -dioxo-Mo­(VI) complex to mimic the electron-transfer chain in the molybdenum enzyme sulfite oxidase (Scheme b) .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…13 Enemark and Kirk et al demonstrated that oxo-molybdenum(V) can be photoactivated via an antenna-mediated eT process by covalently linking the oxo-Mo(V) unit to porphyrin-Fe (III) or Zn(II) complexes. 14,15 Recently, Duhme-Klair et al developed biomimetic molybdenum complexes 16 with appended ruthenium-based photoactive units to facilitate oxygen atom transfer (OAT) catalysis via photo-induced eT ( Fig. 1).…”
mentioning
confidence: 99%